2013
DOI: 10.1637/10342-083112-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Marek's Disease Virus in Different Chicken Populations in Iraq and Indicative Virulence Based on Sequence Variation in the EcoRI-Q (meq) Gene

Abstract: A cross-sectional survey was conducted in six provinces in southern Iraq to determine the point prevalence of Marek's disease virus (MDV) in different chicken populations followed by sequencing the meq gene for phylogenetic analysis and virulence-associated polymorphisms. A total of 109 samples from unvaccinated flocks were analyzed comprising 52 dust and 30 spleen samples from commercial broiler farms and 27 spleens from local layer chickens purchased in the town markets. The overall prevalence of MDV was 49.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
2
22
1
4
Order By: Relevance
“…Yet the ecology of MDV is poorly understood. This is perhaps most clearly exemplified by the conventional wisdom that the virus is ubiquitously found on industrialized poultry farms (Office International des-Epizooties, 2010; Dunn, 2013), despite recent surveillance data suggesting that the virus may not be present on a large fraction of farms (Groves et al, 2008; Wajid et al, 2013; Walkden-Brown et al, 2013; Bettridge et al, 2014; Kennedy et al, 2015b, 2017; Ralapanawe et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Yet the ecology of MDV is poorly understood. This is perhaps most clearly exemplified by the conventional wisdom that the virus is ubiquitously found on industrialized poultry farms (Office International des-Epizooties, 2010; Dunn, 2013), despite recent surveillance data suggesting that the virus may not be present on a large fraction of farms (Groves et al, 2008; Wajid et al, 2013; Walkden-Brown et al, 2013; Bettridge et al, 2014; Kennedy et al, 2015b, 2017; Ralapanawe et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…with studies performed in these other countries (18,38,43,44) showing virus on only a subset of farms. Like Walkden-Brown et al (44), we found that Marek's disease virus concentration in dust increased in broiler flocks as birds aged.…”
Section: Despite the Differences In Rearing Practices Between The Unimentioning
confidence: 68%
“…Marek's disease virus have made it possible to detect and quantify virus collected from field settings (2,3,23). Four studies have used qPCR methods to study field samples to study virus dynamics in Australia (18,38,44) and Iraq (43). There are many differences between chicken and egg production in these countries and in the United States, perhaps most notably that vaccination is nearly universal among commercial farms in the United States.…”
Section: The Development Of Quantitative Polymerase Chain Reaction (Qmentioning
confidence: 99%
“…Son muchos los genes de las aves de los cuales se especula que están relacionados con la respuesta inmune e involucrados en la resistencia o la susceptibilidad frente al VEM, todos son sobre-expresados durante el proceso de replicación viral al interior de la célula y pueden inducir la formación de proteínas que ayudan al cambio morfológico de la célula 40,58 (Figura 2), MEDICINA VETERINARIA Y ZOOTECNIA Uno de los mayores efectos que tienen los genes asociados al virus es la de producir factores quimotácticos de células T para poder infectarlas permitiendo que se presente la enfermedad tumoral en las aves; algunos de los genes involucrados en la resistencia al VEM son la hormona de crecimiento (GH), antígeno 2 de células madre (SCA2) o precursor de antígeno de Linfocito (LY6E), cadena B del complejo mayor de histocompatibilidad por medio de la reducción de la expresión de las glicoproteínas del CMH B clase I (BLB o CD74), CD79B durante la replicación lítica viral como mecanismo de la evasión de la respuesta inmune, esta reducción en la expresión de las moléculas en la superficie celular no se presenta durante la latencia, sin embargo una expresión genómica mínima viral y la integración a los telómeros de la célula hospedera son suficientes para la evasión de la respuesta inmune 27,47,61 .…”
Section: Genes Asociados Con La Susceptibilidad Y Resistencia a La Enunclassified